Pentingnya Pencatatan Keuangan Dan Pembukuan Sederhana PKK RW I Kampung Ringintelu Semarang - Nur Chasanah, Amalia; Fahmi Wardhani, Masitha; Puspitasari, Diana (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Public knowledge about the importance of financial recording and bookkeeping is still very limited. This is also experienced by the community in Ringintelu Ngaliyan Village. Record-keeping that is not yet in progress results in decision making in the household and bookkeeping not being implemented, which of course can lead to vulnerability to poor economic factors. People conditions also have side businesses, so it is necessary to separate bookkeeping for the family and for the business. Based on these problems, activities are held to overcome existing problems. The aim of carrying out community service is to increase understanding for PKK RW I about the importance of financial recording and simple bookkeeping for families in order to create a harmonious family. The expected result is that the community, especially women from PKK RW I Ringintelu, can implement simple financial recording and bookkeeping practices so that they can carry out good financial planning, and can separate bookkeeping for the family and side businesses for those who have businesses.